2015
DOI: 10.1063/1.4935002
|View full text |Cite
|
Sign up to set email alerts
|

Beyond packing of hard spheres: The effects of core softness, non-additivity, intermediate-range repulsion, and many-body interactions on the glass-forming ability of bulk metallic glasses

Abstract: When a liquid is cooled well below its melting temperature at a rate that exceeds the critical cooling rate Rc, the crystalline state is bypassed and a metastable, amorphous glassy state forms instead. Rc (or the corresponding critical casting thickness dc) characterizes the glass-forming ability (GFA) of each material. While silica is an excellent glass-former with small Rc < 10 −2 K/s, pure metals and most alloys are typically poor glass-formers with large Rc > 10 10 K/s. Only in the past thirty years have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 72 publications
0
16
1
Order By: Relevance
“…This functional form ensures that the volume fraction occupied by particles within a given bin size is constant. Such a scaling property has been shown to enhance glass-forming ability in discrete mixtures [57], but we have not tested this hypothesis in great detail for the present systems. Finally, we introduce a second type of continuous particle size distributions, which combine the salient features of both discrete and continuous mixtures.…”
Section: A Algorithm Interactions and Size Distributionsmentioning
confidence: 87%
See 1 more Smart Citation
“…This functional form ensures that the volume fraction occupied by particles within a given bin size is constant. Such a scaling property has been shown to enhance glass-forming ability in discrete mixtures [57], but we have not tested this hypothesis in great detail for the present systems. Finally, we introduce a second type of continuous particle size distributions, which combine the salient features of both discrete and continuous mixtures.…”
Section: A Algorithm Interactions and Size Distributionsmentioning
confidence: 87%
“…Our first analysis of models with continuous polydispersity concerns the role of the particle softness. Previous studies have found that softness can have a nontrivial impact on glass properties, such as fragility [71] and glass-forming ability [57]. Here we simulated polydisperse soft particles varying the softness exponent n using the values n = 8, 12, 18, 24.…”
Section: B Influence Of the Particle Softnessmentioning
confidence: 99%
“…It will also be interesting to investigate systematically how the varying repulsive steepness of interaction affects fragility when the strength of attraction is held fixed as studied in Ref. 38, and how the varying length and strength of attraction influence fragility with the repulsive steepness of interaction unchanged as done in Ref. 39.…”
Section: Discussionmentioning
confidence: 99%
“…For metallic glasses, since there must be other important parameters (stiffness of potential, covalent bonding, etc. ), which go beyond the hard-sphere picture and thus will influence this exponent [22]. Also, the rather high temperature at which the scaling law is normally probed in metallic glasses could also influence the exponent.…”
Section:  mentioning
confidence: 99%
“…In this work, we provide microscopic insight to this problem by studying the three-dimensional packing of spherical granular particles, which is a prototypical hard-sphere glass former and has long been considered as a structural model for metallic glasses [20][21][22]. We identify a non-cubic scaling law in our system, and provide evidences that its origin is local, i.e., without resorting to any fractal structures.…”
mentioning
confidence: 99%